Pulmonary Rehabilitation for Interstitial Lung Disease Associated with Connective Tissue Disease: A Systematic Review of Randomized Controlled Trials and Primary Studies - Yessica Fianita; Yeni Oktasari (International Medical Journal Corp. Ltd, 2026)
Introduction: Connective tissue disease-associated interstitial lung disease (CTD-ILD) is a progressive, disabling condition with high morbidity and mortality. Pulmonary rehabilitation (PR) has emerged as an evidence-based non-pharmacological intervention; however, a comprehensive synthesis specifically addressing CTD-ILD populations across multiple clinically relevant outcome domains remains absent. This systematic review evaluates the efficacy and safety of PR in CTD-ILD across ten outcome domains. Methods: This systematic review was conducted in accordance with PRISMA 2020 guidelines. RCTs and prospective primary studies involving adults with ILD or CTD-ILD receiving structured PR were eligible. Two independent reviewers screened titles/abstracts and full texts. Risk of bias was assessed using Cochrane RoB 2.0 for RCTs and ROBINS-I for non-randomized studies. Narrative synthesis was employed due to heterogeneity in PR programs, ILD subtypes, and outcome instruments. Results: Fifteen studies (13 RCTs, 2 prospective cohorts; n=1,002) published between 2008–2023 met inclusion criteria. PR significantly improved 6-minute walk distance (pooled +40 m, 95% CI 32–47 m; p<0.001), with CTD-ILD subgroups showing +42 m (95% CI 25–60 m) and sustained improvements at 6 months. Health-related quality of life (SGRQ –8 to –12 points), dyspnea, peripheral muscle strength, and fatigue all improved significantly. Pulmonary function (FVC, DLCO) was unchanged. No serious adverse events attributable to PR were recorded. Telerehabilitation and high-intensity interval training demonstrated comparable efficacy to conventional programs. Discussion: PR is safe and effective in CTD-ILD, with improvements in exercise capacity, quality of life, dyspnea, and fatigue. CTD-ILD patients sustain PR benefits longer than IPF patients, reflecting a more variable disease trajectory. Both HIIT and MICT yield comparable outcomes. Evidence is limited by heterogeneous CTD-ILD subgroup representation, small sample sizes, and short follow-up durations. The exercise capacity–physical activity translational gap requires targeted behavioral interventions. Conclusions: PR significantly improves exercise capacity, quality of life, dyspnea, and fatigue in CTD-ILD and is safe when appropriately supervised. Dedicated RCTs specifically designed for CTD-ILD subgroups are urgently needed to establish disease-specific PR protocols and long-term maintenance strategies.